Phosphorus-doped carbon nitride composite CdS-CdIn2S4 composite photocatalyst as well as preparation method and application thereof
By preparing the phosphorus-doped carbon nitride composite CdS@CdIn2S4 composite photocatalyst, the nano-scale contact interface and dual Z-type heterojunction mechanism are used to solve the problem of low hydrogen production efficiency of existing sulfur-doped carbon nitride photocatalysts, and the effect of efficient photocatalytic hydrogen production is achieved.
Patent Information
- Application Number
- CN202510132333.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-04-29
AI Technical Summary
The actual hydrogen production efficiency of existing sulfur-doped carbon nitride photocatalysts in photocatalytic hydrogen production is not high, and the preparation method is complex and costly.
By preparing the phosphorus-doped carbon nitride composite CdS@CdIn2S4 composite photocatalyst, the nano-scale contact interface and dual Z-type heterojunction mechanism of ultra-thin g-C3N4 and CdS@CdIn2S4 composite materials are used to improve the photocatalytic performance.
The photocatalytic performance was significantly improved, the hydrogen production efficiency reached 7614μmol·g-1·h-1, and good stability was maintained.
Smart Images

Figure CN119897143A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalysts, in particular to a phosphorus-doped carbon nitride composite CdS@CdIn2S4 composite photocatalyst and a preparation method and application thereof. Background Art
[0002] In recent years, non-metallic semiconductor photocatalyst graphite carbon nitride (g-C3N4) materials have come into people's view. Since the sp hybridized C and N atoms in the g-C3N4 structure form a certain conjugated system, it has excellent thermal stability, chemical stability and other properties. In addition, g-C3N4 can also absorb visible light, the preparation process is simple and low-cost, and it can catalyze the decomposition of water to produce hydrogen under visible light irradiation and triethanolamine as a hole scavenger. There is room for great development in the field of photocatalytic hydrogen production. However, g-C3N4 has disadvantages such as low specific surface area, wide band gap of about 2.72eV, easy recombination of photogenerated electrons and holes, and low conductivity, which leads to limited catalytic activity, so it needs to be modified. At present, g-C3N4 can be modified by doping (metal, non-metal, precious metal, etc.) for morphology control, loading of co-catalysts, etc., and regulating the composition of the material or changing the specific surface area and other properties to improve the above shortcomings, thereby improving the photocatalytic activity. When g-C3N4 is sulfur-doped, by regulating the composition, electronic structure and thickness of g-C3N4, the specific surface area can be increased while causing certain defects, exposing more active sites, and improving the performance of photocatalytic hydrogen production. Chinese Patent Publication No. CN111185216A discloses mixing melamine and thiocyanuric acid in a solvent, and then performing a hydrothermal reaction to obtain a solid tubular composite, and then calcining with urea to obtain a hollow tubular sulfur-doped carbon nitride / graphite phase carbon nitride homojunction photocatalyst. Chinese Patent Publication No. CN107930667A discloses a method for preparing sulfur-doped carbon nitride by dissolving melamine and thiocyanuric acid in hot water, mixing them evenly, and calcining them after hydrothermal reaction. These disclosed preparation methods have cumbersome and complicated steps, require post-processing, and are relatively costly.
[0003] Although the above catalysts can also improve the photocatalytic performance of carbon nitride, their actual hydrogen production efficiency is still not high. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a phosphorus-doped carbon nitride composite CdS@CdIn2S4 composite photocatalyst and a preparation method and application thereof to achieve efficient photocatalytic hydrogen production.
[0005] To achieve the above object, the present invention is implemented according to the following technical solutions:
[0006] One of the technical solutions of the present invention is a method for preparing a phosphorus-doped carbon nitride composite CdS@CdIn2S4 composite photocatalyst, comprising the following steps:
[0007] S1, preparation of phosphorus-doped g-C3N4, denoted as PCN;
[0008] S2, preparation of CdS@CdIn2S4 composite material, denoted as CSCIS;
[0009] S3. Disperse the PCN and CdS@CdIn2S4 composite material with a mass ratio of (7-9): (1-3) in 60 mL of deionized water and stir for 30 min. Then transfer it to a 100 mL high-pressure reactor with a polytetrafluoroethylene liner, heat it to 140°C and keep it warm for 12 h. After the reactor is cooled to room temperature, wash it three times with deionized water and anhydrous ethanol each and dry it to obtain a composite photocatalyst PCN / CdS@CdIn2S4, denoted as PCNCSCIS.
[0010] Furthermore, the step S1 specifically includes:
[0011] S11, dissolving 20 g of urea in a crucible filled with 15 mL of deionized water, covering the crucible with a lid and transferring it to a muffle furnace, raising the temperature to 550°C and keeping it for 3 h; then cooling it to room temperature to obtain ultrathin g-C3N4, recorded as CN;
[0012] S12. Dissolve 1 g of CN and 0.5 g of anhydrous sodium hypophosphite in a beaker filled with 80 mL of deionized water, and then place the beaker in an oil bath at 70°C to evaporate to dryness; after evaporation, place the sample in a porcelain boat and send it into a tube furnace, raise the temperature to 400°C, and keep it warm for 2 hours; after the sample is cooled to room temperature, wash it three times with deionized water and anhydrous ethanol each, and then send it into a drying oven at 60°C to dry for 12 hours to obtain PCN.
[0013] Furthermore, the step S2 specifically includes:
[0014] S21, adding 10 mmol of thiocyanate and 30 mmol of sodium hydroxide into a beaker filled with 200 mL of deionized water and stirring, then placing the beaker in an oil bath at 60° C. and stirring for 2 h to obtain solution A;
[0015] S22, add 15 mmol of CdCl2 and 200 mL of deionized water into a 500 mL beaker and stir to obtain solution B;
[0016] S23, gradually dripping the heated and stirred solution A into solution B, the solution gradually turns white and is stirred for 24 hours; then washing with deionized water 6 times and drying to obtain the precursor of CSCIS Cd3(C3N3S3)2;
[0017] S24. Put 1.5 mmol of Cd3(C3N3S3)2 and 80 mL of deionized water into a beaker and ultrasonicate for 15 min, then add 1 mmol of InCl3 and stir for 15 min. Then transfer the solution to a 100 mL high-pressure reactor with a polytetrafluoroethylene liner, heat to 140 °C and keep warm for 12 h. After the reactor is cooled to room temperature, wash it with deionized water and anhydrous ethanol three times each and vacuum dry it to obtain CSCIS.
[0018] Preferably, the heating rate in the muffle furnace is 5°C / min.
[0019] The second technical solution of the present invention is a phosphorus-doped carbon nitride composite CdS@CdIn2S4 composite photocatalyst prepared by the above method.
[0020] The third technical solution of the present invention is the application of phosphorus-doped carbon nitride composite CdS@CdIn2S4 composite photocatalyst in photocatalytic water hydrogen production.
[0021] Compared with the prior art, the present invention prepares ultra-thin carbon nitride by recrystallizing urea through thermal polymerization, then doping P element into carbon nitride (PCN) to adjust the band structure of carbon nitride, and then compounding PCN with CdS@CdIn2S4 (CSCIS) to form PCN / CdS@CdIn2S4 ternary heterogeneous material (PCNCSCIS). After the two-dimensional nanosheet CdS@CdIn2S4 is compounded with ultra-thin PCN, a large number of nanoscale contact interfaces are formed, and a rich heterogeneous structure is constructed. This structure not only enhances the scattering and refraction probability of light, significantly improves the light utilization rate, but also effectively promotes the separation and transmission of photogenerated carriers by forming a double Z-type heterojunction mechanism, thereby improving the photocatalytic performance, and the hydrogen production efficiency is as high as 7614μmol·g -1 ·h -1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 CSCIS scanning electron microscope image of two-dimensional nanosheet stacking.
[0023] Figure 2 Scanning electron microscope image of ultrathin PCN.
[0024] Figure 3 This is a scanning electron microscope image of the composite photocatalyst sample 9PCNCSCIS.
[0025] Figure 4 These are the X-ray diffraction patterns of ultrathin PCN, CSCIS, composite photocatalyst sample 7PCNCSCIS, composite photocatalyst sample 8PCNCSCIS and composite photocatalyst sample 9PCNCSCIS.
[0026] Figure 5 These are the steady-state fluorescence spectra of CN, ultrathin PCN, CS, CIS, CSCIS, composite photocatalyst sample 7PCNCSCIS, composite photocatalyst sample 8PCNCSCIS and composite photocatalyst sample 9PCNCSCIS.
[0027] Figure 6 These are the photocatalytic hydrogen production rate diagrams of ultra-thin PCN, CS, CIS, composite photocatalyst sample 7PCNCSCIS, composite photocatalyst sample 8PCNCSCIS and composite photocatalyst sample 9PCNCSCIS.
[0028] Figure 7 This is a photocatalytic performance stability diagram of ultra-thin PCN, CS, CIS, composite photocatalyst sample 7PCNCSCIS, composite photocatalyst sample 8PCNCSCIS and composite photocatalyst sample 9PCNCSCIS. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the invention.
[0030] The raw materials used in the following examples include: thiocyanuric acid (C3H3N3S3), sodium hydroxide (NaOH), cadmium chloride (CdCl2), indium trichloride (InCl3), urea (NH2CONH2), sodium hypophosphite (NaH2PO2), anhydrous ethanol, deionized water, triethanolamine (TEOA, >99%). All raw materials were purchased from Aladdin and McLean.
[0031] Example 1
[0032] 1) Synthesis of PCN
[0033] Put 20g of urea and 15mL of deionized water into a crucible with a capacity of 50mL, and stir for thirty minutes until the urea melts into the water; cover the crucible with a lid and transfer it to a muffle furnace, heat it to 550℃ at a heating rate of 5℃ / min, and keep it warm for 3h; after the sample cools to room temperature, CN can be obtained; then add 1g of CN and 0.5g of anhydrous sodium hypophosphite to a beaker with a capacity of 200mL, and add 80mL of deionized water to the beaker; use a magnetic stirrer to mix the CN and anhydrous sodium hypophosphite in the beaker evenly, and then place the beaker in an oil bath pot at 70℃ to evaporate; after evaporation, place the sample in a porcelain boat and send it into a tubular furnace, heat it to 400℃ at a heating rate of 5℃ / min, and keep it warm for 2h; after the sample cools to room temperature, use deionized water and anhydrous ethanol to wash it three times each and send it into a drying oven at 60℃, and PCN can be obtained after drying for 12h.
[0034] 2) Synthesis of CdS@CdIn2S4 composite materials
[0035] 10 mmol of trithiocyanate, 30 mmol of sodium hydroxide and 200 mL of deionized water were placed in a beaker and stirred, and then placed in an oil bath at 60°C and stirred for 2 hours to obtain solution A; 15 mmol of CdCl2 and 200 mL of deionized water were placed in a beaker with a capacity of 500 mL and stirred to obtain solution B. The heated and stirred solution A was gradually dripped into solution B, the solution gradually turned white and was stirred for 24 hours; then it was washed with deionized water for 6 times and dried to obtain the precursor of CSCIS Cd3(C3N3S3)2(CS), and then 1.5mmol of Cd3(C3N3S3)2 and 80mL of deionized water were put into a beaker and ultrasonicated for 15 minutes; then 1mmol of InCl3 was added and stirred for 15 minutes, and then the solution was transferred to a 100mL high-pressure reactor with a polytetrafluoroethylene liner, heated to 140°C and kept warm for 12 hours; after the reactor was cooled to room temperature, it was washed with deionized water and anhydrous ethanol three times each and vacuum dried to obtain CSCIS.
[0036] 3) Synthesis of PCN / CdS@CdIn2S4
[0037] 0.1g of CSCIS and 0.9g of PCN were dispersed in 60mL of deionized water and stirred for 30min, then transferred to a 100mL high-pressure reactor with a polytetrafluoroethylene liner, heated to 140°C and kept warm for 12h. After the reactor was cooled to room temperature, it was washed three times with deionized water and anhydrous ethanol and dried to obtain the composite photocatalyst sample 9PCNCSCIS.
[0038] Example 2
[0039] The difference from Example 1 is: 3) Synthesis of PCN / CdS@CdIn2S4
[0040] 0.3 g of CSCIS and 0.7 g of PCN were dispersed in 60 mL of deionized water and stirred for 30 min, then transferred to a 100 mL high-pressure reactor with a polytetrafluoroethylene liner, heated to 140 ° C and kept warm for 12 h. After the reactor was cooled to room temperature, it was washed three times with deionized water and anhydrous ethanol and dried to obtain the composite photocatalyst sample 7PCNCSCIS.
[0041] Example 3
[0042] The difference from Example 1 is: 3) Synthesis of PCN / CdS@CdIn2S4
[0043] 0.2g of CSCIS and 0.8g of PCN were dispersed in 60mL of deionized water and stirred for 30min, then transferred to a 100mL high-pressure reactor with a polytetrafluoroethylene liner, heated to 140°C and kept warm for 12h. After the reactor was cooled to room temperature, it was washed three times with deionized water and anhydrous ethanol and dried to obtain the composite photocatalyst sample 8PCNCSCIS.
[0044] The CSCIS scanning electron microscope image of the two-dimensional nanosheet stack prepared in the above embodiment is as follows: Figure 1 As shown by Figure 1 It can be seen that the CSCIS composite material presents a 2D interlaced structure as a whole. The scanning electron microscope image of the ultrathin PCN is shown in Figure 2. Figure 2 As shown by Figure 2 It can be seen that the PCN sample presents an ultra-thin sheet structure. Taking the composite photocatalyst sample 9PCNCSCIS prepared in Example 1 as an example, its scanning electron microscope image is as follows Figure 3 As shown by Figure 3 It can be seen that the composite photocatalyst sample 9PCNCSCIS is composed of ultra-thin sheets of PCN and sheets of interwoven CdS-CdIn2S4 stacked together. The X-ray diffraction patterns of ultra-thin PCN, CSCIS and composite photocatalyst sample 9PCNCSCIS are shown in Figure 2. Figure 4 As shown by Figure 4 It can be seen that the diffraction spectrum of the composite photocatalyst sample 9PCNCSCIS contains the characteristic peaks of PCN, CS and CIS, indicating that the structures of PCN and CSCIS are not destroyed. The steady-state fluorescence spectra of CN, ultrathin PCN, CS, CIS, CSCIS and the composite photocatalyst sample 9PCNCSCIS are shown in Figure 2. Figure 5 As shown by Figure 5It can be seen that the vibration peak of CN and the characteristic peaks of CS and CIS in the composite photocatalyst sample 9PCNCSCIS are preserved, which shows that g-C3N4 and CSCIS are successfully composited and the chemical structures of g-C3N4 and CSCIS have not changed.
[0045] Application Example 1
[0046] 90 mL of deionized water and 10 mL of triethanolamine (TEOA) solution by volume were added into the reactor, followed by the addition of 25 mg of the composite photocatalyst sample 9PCNCSCIS for stirring, and then 1 mL of 1 mg / mL chloroplatinic acid (H2PtCl6·6H2O, Pt: 37.5%) was added as a co-catalyst; the reactor was immediately sealed, and nitrogen (N2) was introduced into the reactor for 15 minutes to blow away all the air in the reactor; the reaction device was then sealed and transferred to a 300 W xenon lamp with a 420 nm cutoff filter for photodeposition, and a water circulation system was used to keep the temperature of the reactor below 30°C. After thirty minutes, chloroplatinic acid could load 1 wt% Pt on the catalyst; after the photodeposition was completed, 0.6 mL of gas was extracted every hour to test the hydrogen content, and a total of four hours of gas was extracted; the hydrogen content was tested using a gas spectrometer with N2 as a carrier gas and a TCD detector.
[0047] Application Example 2
[0048] The difference from Application Example 1 is that the composite photocatalyst sample 7PCNCSCIS is added.
[0049] Application Example 3
[0050] The difference from Application Example 1 is that the composite photocatalyst sample 8PCNCSCIS is added.
[0051] Comparative application example 1
[0052] The difference from Application Example 1 is that ultra-thin PCN is added.
[0053] Comparative Application Example 2
[0054] The difference from Application Example 1 is that CS is added.
[0055] Comparative application example 1
[0056] The difference from Application Example 1 is that CIS is added. The preparation process of CIS is as follows: first, 0.4mmolCdCl2 and 0.8mmolthioacetamide are added to a beaker, and then 15ml of deionized water and 15ml of ethanol are added to the beaker and stirred evenly, and then transferred to a 100mL high-pressure reactor with a polytetrafluoroethylene liner, heated to 160°C and kept warm for 16 hours. After the reactor is cooled to room temperature, it is washed three times with deionized water and anhydrous ethanol and dried, and the sample CdIn2S4 (abbreviated as CIS) is prepared.
[0057] The photocatalytic hydrogen production rates of ultra-thin PCN, CS, CIS, composite photocatalyst sample 7PCNCSCIS, composite photocatalyst sample 8PCNCSCIS and composite photocatalyst sample 9PCNCSCIS are shown in the figure. Figure 6 As shown by Figure 6 It can be seen that the composite photocatalyst sample 8PCNCSCIS has the highest yield, which can reach 7614 μmol·g-1·h-1.
[0058] Taking the composite photocatalyst sample 8PCNCSCIS as an example, the photocatalytic hydrogen production of the composite photocatalyst sample 8PCNCSCIS was tested. After five cycles, each cycle lasted for four hours. The catalytic hydrogen production yield is shown in the figure below. Figure 7 As shown by Figure 7 It can be seen that after five cycles, the photocatalyst of the present invention still has good photocatalytic hydrogen production stability and photocatalytic hydrogen production activity, indicating that the catalyst of the present invention has good stability.
[0059] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.
Claims
1. A method for preparing a phosphorus-doped carbon nitride composite CdS@CdIn2S4 composite photocatalyst, characterized in that: The following steps are involved: S1, preparation of phosphorus-doped g-C3N4, denoted as PCN; S2, preparation of CdS@CdIn2S4 composite material, denoted as CSCIS; S3. Disperse the PCN and CdS@CdIn2S4 composite material with a mass ratio of (7-9): (1-3) in 60 mL of deionized water and stir for 30 min. Then transfer it to a 100 mL high-pressure reactor with a polytetrafluoroethylene liner, heat it to 140°C and keep it warm for 12 h. After the reactor is cooled to room temperature, wash it three times with deionized water and anhydrous ethanol each and dry it to obtain a composite photocatalyst PCN / CdS@CdIn2S4, denoted as PCNCSCIS.
2. The method for preparing the phosphorus-doped carbon nitride composite CdS@CdIn2S4 composite photocatalyst according to claim 1, characterized in that: The step S1 specifically includes: S11, dissolving 20 g of urea in a crucible filled with 15 mL of deionized water, covering the crucible with a lid and transferring it to a muffle furnace, raising the temperature to 550°C and keeping it for 3 h; then cooling it to room temperature to obtain ultrathin g-C3N4, recorded as CN; S12. Dissolve 1 g of CN and 0.5 g of anhydrous sodium hypophosphite in a beaker filled with 80 mL of deionized water, and then place the beaker in an oil bath at 70°C to evaporate to dryness; after evaporation, place the sample in a porcelain boat and send it into a tube furnace, raise the temperature to 400°C, and keep it warm for 2 hours; after the sample is cooled to room temperature, wash it three times with deionized water and anhydrous ethanol each, and then send it into a drying oven at 60°C to dry for 12 hours to obtain PCN.
3. The method for preparing the phosphorus-doped carbon nitride composite CdS@CdIn2S4 composite photocatalyst according to claim 1, characterized in that: The step S2 specifically includes: S21, adding 10 mmol of thiocyanate and 30 mmol of sodium hydroxide into a beaker filled with 200 mL of deionized water and stirring, then placing the beaker in an oil bath at 60° C. and stirring for 2 h to obtain solution A; S22, add 15 mmol of CdCl2 and 200 mL of deionized water into a 500 mL beaker and stir to obtain solution B; S23, gradually dripping the heated and stirred solution A into solution B, the solution gradually turns white and is stirred for 24 hours; then washing with deionized water 6 times and drying to obtain the precursor of CSCIS Cd3(C3N3S3)2; S24. Put 1.5 mmol of Cd3(C3N3S3)2 and 80 mL of deionized water into a beaker and ultrasonicate for 15 min, then add 1 mmol of InCl3 and stir for 15 min. Then transfer the solution to a 100 mL high-pressure reactor with a polytetrafluoroethylene liner, heat to 140 °C and keep warm for 12 h. After the reactor is cooled to room temperature, wash it with deionized water and anhydrous ethanol three times each and vacuum dry it to obtain CSCIS.
4. The method for preparing the phosphorus-doped carbon nitride composite CdS@CdIn2S4 composite photocatalyst according to claim 2, characterized in that: The heating rate in the muffle furnace is 5°C / min.
5. A phosphorus-doped carbon nitride composite CdS@CdIn2S4 composite photocatalyst prepared by the method according to any one of claims 1 to 4.
6. Use of the phosphorus-doped carbon nitride composite CdS@CdIn2S4 composite photocatalyst as claimed in claim 5 in photocatalytic water hydrogen production.
Citation Information
Patent Citations
Sulfur-doped g-C3N4 / TiO2 heterojunction photocatalyst, and preparation method and application thereof
CN107930667A
Hollow tubular sulfur-doped carbon nitride / graphite-phase carbon nitride homojunction photocatalyst, and preparation method and application thereof
CN111185216A